Quantification of rehabilitation for patients with Parkinson’s disease and related disorders using wearable devices; a proof of concept - Kamo, Hikaru; Oyama, Genko; Nagaki, Koichi; Hattori, Nobutaka (Frontiers in Neurology, 2025)
IntroductionTo date, disease-modifying therapies have not been established for Parkinson’s disease (PD) or atypical parkinsonisms. Exercise has been reported to help maintain functional abilities and delay disease progression. However, no consensus exists regarding the type, amount, or timing of exercise for each disease stage. Therefore, this study aimed to quantify rehabilitation interventions and identify optimal approaches based on patient characteristics.MethodsParticipants diagnosed with PD or related disorders and residing in an elderly care facility received various rehabilitation therapies—including water stimulation bed, therapeutic massage, sit-to-stand training, gait training, cycle ergometer training, aerobic training using treadmill, stretching, balance training, calisthenics, and resistance training—while wearing a wearable device between April and May 2022. The following parameters were evaluated: differences in body surface temperature and pulse rate before and after rehabilitation, calories burned, steps taken during rehabilitation, and upper and lower extremity activity indices.ResultsA total of 49 participants were included, and the frequency of rehabilitation sessions was determined at the discretion of the therapist based on each participant’s condition. Each rehabilitation session was quantified and visualized using radar charts.DiscussionThis study offers insight into the quantification and visualization of rehabilitation effects in patients with progressive neurodegenerative diseases presenting with parkinsonism. Future efforts should focus on accumulating data under standardized conditions and assessing motor symptoms longitudinally to develop personalized rehabilitation programs for patients with neurodegenerative disorders.